To solve the equation \(-\frac{3}{5}x = \frac{2}{5}\) using inverse operations, we need to isolate \(x\).
-
Start with the equation: \[ -\frac{3}{5}x = \frac{2}{5} \]
-
To isolate \(x\), multiply both sides by the reciprocal of \(-\frac{3}{5}\), which is \(-\frac{5}{3}\): \[ x = \frac{2}{5} \cdot -\frac{5}{3} \]
-
Multiply the fractions: \[ x = -\frac{2 \cdot 5}{5 \cdot 3} = -\frac{10}{15} \]
-
Simplify \(-\frac{10}{15}\): \[ x = -\frac{2}{3} \]
The solution \(x = -\frac{2}{3}\) means we need to check which answer option corresponds to this fraction.
Looking at the answer choices:
- A: \(-15 \frac{1}{5}\)
- B: \(23\frac{2}{3}\)
- C: \(-23-\frac{2}{3}\)
- D: \(-625-\frac{6}{25}\)
The answer that matches \(x = -\frac{2}{3}\) is in option C: \(-23 - \frac{2}{3}\).
Thus, the correct answer is C.